Therapeutic vulnerabilities among KRAS G12C mutant (mut) advanced cancers based on co-alteration (co-alt) patterns - Nusrat, Maliha; Roszik, Jason; Holla, Vijaykumar; Cai, Tiantian; Hong, Meiyue; Coker, Oluwadara; Johnson, Benny; Rodon Ahnert, Jordi; Janku, Filip; Kopetz, Scott; Shaw, Kenna Rael; Meric-Bernstam, Funda; et al. (Journal of clinical oncology, 2020)
Abstract only 3625 Background: Oncogenic KRAS mut drive cancers and confer therapeutic resistance by activating MAPK signaling. Inhibiting KRAS has been elusive until the recent promising phase I trials with KRAS G12C inhibitors (i). We characterized frequencies of KRAS G12C mut and gene co-alt among advanced cancer patients (pts) to identify therapeutic vulnerabilities for combination development. Methods: We analyzed next generation sequencing datasets from MD Anderson Cancer Center (MDACC, n = 42,316) and AACR GENIE (n = 56,970). Genes and individual alterations were annotated for potential actionability with approved or investigational drugs and grouped into 12 oncogenic pathways. Frequencies of potential drug combinations with KRAS G12Ci were estimated per tumor type based on co-occurrence of potentially actionable alterations. Results: KRAS G12C was present in 850/34,801 (2.4%) advanced solid tumor and 22/7698 (0.3%) hematologic malignancy pts in MDACC dataset; and 1422 (2.5%) pts in AACR GENIE. Among solid tumor pts, 798 had histology data and 640 had ≥46 gene profiling. Most common cancers were non-small cell lung (NSCLC, 67%), colorectal (CRC, 24%), other gastrointestinal (oGI, 4%) and gynecologic (gyn, 2%). KRAS G12C prevalence was 19.5% (441/2265) in NSCLC and 4.2% (146/3469) in CRC. Genes most commonly co-altered were TP53 (42%), STK11 (17%) and MET (11%) in NSCLC; TP53 (58%), APC (54%) and PIK3CA (24%) in CRC; TP53 (42%), APC (21%) and ATM (21%) in oGI; TP53 (56%), PIK3CA (25%), and PTEN (19%) in gyn cancers. These co-alt did not impact overall survival. In both datasets, as compared to KRAS wild, KRAS G12C was significantly co-altered with STK11 in NSCLC; PIK3CA and SMAD4 in CRC (P < 0.05 for all). EGFR mut in NSCLC and BRAF mut in CRC rarely co-occurred with KRAS G12C (P < 0.01). Most frequently co-altered oncogenic pathways in NSCLC, CRC, oGI and gyn cancers respectively included PI3K (27, 32, 33, 44 %), receptor tyrosine kinases (13, 16, 42, 13 %) and DNA damage repair (12, 10, 38, 19 %). Potentially actionable co-alt frequencies suggest that combining KRAS G12Ci with mTORi or PI3Ki would be indicated most frequently, in 24% and 13% of all pts respectively. Conclusions: KRAS G12Ci development is most relevant for NSCLC, gastrointestinal and gyn cancers. The co-alt patterns highlight relevant oncogenic pathways and candidate drugs for future combination therapies. Co-inhibition of PI3K-mTOR and MAPK pathways has shown synergism in prior pre-clinical studies but had poor tolerance in pts. There is opportunity to revisit this approach with the new KRAS G12Ci.